Aplicação de produtos da fermentação e ultrabaixo oxigênio para a conservação de maçãs royal gala - Weber, Anderson (2010)
The aim of this work was to evaluate the effect of post harvest ethanol or acetaldehyde application and to compare them with consolidated storage techniques on the quality maintenance of Royal Gala‟ apples. Also, we aimed to evaluate the effect of controlled atmosphere condition with ultra low oxygen partial pressures on the post storage quality maintenance of Royal Gala‟ apples. To reach such aims, three experiments were performed during 2008 and 2009. In the first experiment, carried out in 2008, the following treatments were evaluated: [1] control; [2] application of 0.5mL of ethanol month-1 kg-1; [3] application of 0.25mL acetaldehyde month-1 kg-1; [4] application of 625 ηL L-1 1-MCP; and [5] ethylene scrubbing (<0.02μL L-1). All fruits from the evaluated treatments were stored in CA with 1.0kPa O2 and 2.0kPa CO2. In the second experiment, carried out in 2009, the treatments were constituted in the following way: [1] control; [2] low relative air humidity (LRH); [3] LRH and application of 0.3mL of ethanol month-1 kg-1; and [4] application of 0.3mL of ethanol month-1 kg-1. All treatments were stored in CA with 1.2kPa O2 associated with 2.5kPa CO2. In the two experiments the fruits were stored at 0.5°C. In the third experiment, carried out in 2008, five CA conditions were evaluated: [1] 1.0kPa O2 and 2.0kPa CO2; [2] 0.8kPa O2 and 1.5kPa CO2; [3] 0.8kPa O2 and 1.0kPa CO2; [4] 0.6kPa O2 and 1.5kPa CO2; and [5] 0.6kPa O2 and 1.0kPa CO2. All conditions were stored in 0.0°C, 0.5°C and 1.0°C resulting in a factorial experiment. The application of 0.5mL ethanol month-1 kg-1 or 0.25mL acetaldehyde month-1 kg-1 cause increase in mealiness, flesh browning and rottenness incidence and decrease flesh firmness, resulting in decrease in the quality maintenance when compared with the application of 1-MCP and ethylene scrubbing. However, 0.3mL ethanol month-1 kg-1, performed on second experiment, resulted in higher flesh firmness retention, lower ACC oxidase activity and lower ethylene production. The lower relative air humidity is not efficient in maintain apple quality, however, it potentiated the effect of the application of 0.3mL ethanol month-1 kg-1. Royal Gala‟ apples stored in CA with O2 partial pressures below to 0.8kPa show lesser quality after storage. Temperature of 1.0ºC, compared with 0.0°C and 0.5°C, provided highest apple quality maintenance after eight months of storage and more seven days in shelf life at 20ºC. The best ULO condition for fruits stored at 1.0ºC is 1.0kPa O2 with 2.0kPa CO2. The interaction between ULO and storage temperature showed a necessity to increase O2 partial pressures when the storage temperature was increased. This behavior were verified especially when ACC oxidase activity and flesh browning incidence were analyzed.